Perbandingan Perilaku Harian Sapi Potong pada Alas Kandang yang Berbeda - Kasiyati, Kasiyati; Muhammad, Fuad; Hidayat, Jafron Wasiq; Rahadian, Rully; Maryono, Maryono (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2026)
Using appropriate bedding can enhance the welfare of beef cattle. This study was designed to evaluate the daily behavior of beef cattle kept on different types of bedding. Field research was conducted over a period of two months, using eight beef cattle, which were divided into two groups based on the type of bedding used, namely straw and rubber mats. The daily behaviors observed were the duration and frequency of eating, aggressive behavior, lying down, sleeping, standing, and elimination. The observation used was an intermittent method. The first group consisted of a pen block with straw bedding, and the second group consisted of a pen block with carpet bedding. Data analysis used the t-test and analysis of variance at a significance level of 5%. The results showed that all parameters did not reveal any differences; however, sleeping behavior was higher (P < 0.05) in the straw-bedded pens, with the highest percentage of sleep occurring in the afternoon. This study concluded that both straw and rubber carpet bedding are still capable of supporting the normal expression of the main daily behaviors of cows. Both types of bedding are still suitable for use in beef cattle husbandry systems.